2004
DOI: 10.1007/s11745-004-1275-6
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation and delivery of n−3 fatty acids through spray‐dried milk reduce serum and liver lipids in rats

Abstract: Indian diets comprising staples such as cereals, millets, and pulses provide 4.8 energy % from linoleic acid (18:2n-6) but fail to deliver adequate amounts of n-3 FA. Consumption of long-chain n-3 PUFA such as EPA (20:5n-3) and DHA (22:6n-3) is restricted to those who consume fish. The majority of the Indian population, however, are vegetarians needing additional dietary sources of n-3 PUFA. The present work was designed to use n-3 FA-enriched spray-dried milk powder to provide n-3 FA. Whole milk was supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
5
3
0
Order By: Relevance
“…Adipose tissue accumulated high levels of ALA from dietary lipids but it was not converted to EPA or DHA. These results are in agreement with earlier reports (Ramaprasad et al . 2004), where it was shown that rats given diet containing 25% ALA accumulated ALA to an extent of 12% of the total fatty acids in adipose tissue, but it was not converted to EPA and DHA.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Adipose tissue accumulated high levels of ALA from dietary lipids but it was not converted to EPA or DHA. These results are in agreement with earlier reports (Ramaprasad et al . 2004), where it was shown that rats given diet containing 25% ALA accumulated ALA to an extent of 12% of the total fatty acids in adipose tissue, but it was not converted to EPA and DHA.…”
Section: Discussionsupporting
confidence: 94%
“…The arachidonic acid is a product of D 6 and D 5 desaturation and elongation of 18:2 w-6, while 18:3 w-3 is elongated and desaturated to EPA and DHA. The ability of 18:3 w-3 to reduce the level of 18:2 w-6 and 20:4 w-6 has been recorded in earlier studies (Ramaprasad et al 2004). Our current study and that of Ramaprasad et al (2010) that ALA from the diet was taken up and marginally converted to longchain omega-3 fatty acids in serum and liver.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…GCO, when fed as the sole source of lipid in the diet showed relatively higher hypolipidemic effect compared to GCO blended oils with other vegetable oils. Reduced serum TG levels were reported in rats fed with ALA rich vegetable oils viz., chia oil (Ayerza & Coates, 2007), perilla oil (Kim, Choi, & Choi, 2004) and linseed oil (Ramaprasad, Baskaran, Sambaiah, & Lokesh, 2004). RBO and SESO blends with GCO showed relatively more hypolipidemic effect than SFO blended oil because of combined effect of ALA and other minor components such as ozyanol present in RBO, sesamol, sesamin and sesamolin present in SESO and high tocols present in GCO compared to other blended oils.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the vegetable oils that are being consumed are rich in n-6 PUFAs and deficient in n-3 PUFAs with the n-6 to n-3 PUFA ratio of 50:1. In order to increase n-3 PUFA levels in diet, linseed oil and fish oil are supplemented in milk based formulations (Ramaprasad et al 2004) and blending of α-linolenic acid (ALA 18:3) rich oils with edible vegetable oils are being attempted (Umesha and Naidu 2012). However, n-3 PUFAs are highly unsaturated, susceptible to autoxidation under aerobic conditions (Fritsche and Johnston 1988), cause an increase in oxidative stress through ROS production (Costabile et al 2005) and also ameliorate antioxidant defense system (Venkatraman and Pinnavaia 1998).…”
Section: Introductionmentioning
confidence: 99%